Whose party is it anyway? An invitation from a patient experience advocate - Geoffrey Silvera (The Beryl Institute, 2023)
In this commentary, the associate editor of Patient Experience Journal (PXJ) discusses the need to center the human experience in health care by celebrating its essential human, the patient. We have a duty to honor and uphold the dignity of the importance of patient priorities, needs, and preferences, and those of their families. We honor, empower, and celebrate the patient experience at the Patient Experience Journal. We do this not only for the sake of patients, but for our sakes as well, so that we might all delight in patient-centered healthcare systems across the globe. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.